PERWUJUDAN BUDAYA INDIS PADA INTERIOR GEREJA KRISTEN JAWI WETAN MOJOWARNO - Mulyono, Grace; Mandasari, Yohana (Dimensi Interior, 2011)
The Dutch colony in Indonesia has incited cultural lifestyle formations of the Indies. The architecture of Jawi Wetan Mojowarno Christian Church as one of the legacy of Indies culture has been built since 1881 and has adopted two distinctly different cultures, which are local culture and colonial culture. This research paper discusses the influences and appearance of this Indies culture on the interior design of Jawi Wetan Mojowarno Christian Church using the qualitative descriptive method. The results showed that Mojowarno church had adopted the European trends in style at the time it was built, such as Gothic and Neo- Classic that were combined with the local culture.